Kajian Kegagalan Komponen Dan Perawatan Pada Sistem Pelumas Mesin Diesel Di Kapal - Ratna Indriyani; Dwisetiono Dwisetiono (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
The diesel engine as the main engine on the ship can function properly if it is supported by good supporting systems such as a lubricating oil system. The lubricant system is one of the most important systems in ship operation, failure in the lubrication system causes the system to not operate properly and can suffer losses from the ship. This study aims to determine the failure of each component of the lubricating system in the main engine and its proper maintenance. This study was conducted using the Failure Mode and Effect Analysis (FMEA) method to optimize the way to overcome the failure and maintenance of the ship's main engines to identify strategies and maintenance priorities. By using FMEA, we can determine the failure and the effect caused by each component and to perform maintenance must classify components based on low to high risk levels. The components of lubricating oil tank and sump tank have a low risk, lubricating oil cooler has a moderate risk and lubricating oil pump, lubricating oil filter, purifier, transfer pump and lubricating purifier heater have a high risk. The results of the failure of lubricant system components are very useful in identifying maintenance strategies based on the level of risk of these components by choosing between preventive maintenance and corrective maintenance.